1991
DOI: 10.1093/ajcn/53.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure is increased in stable, malnourished HIV-infected patients

Abstract: Resting energy expenditure (REE) was measured by reference to body composition in 50 malnourished patients with human immunodeficiency virus (HIV) infection and compared with that of 14 healthy subjects. Among HIV patients, 40 had acquired immune deficiency syndrome (AIDS) and 10 had AIDS-related complex (ARC). All were in stable condition and had a previous history of progressive wasting, ie, a mean body weight loss of 14.2 +/- 8.1 kg over 16.6 mo (range 2-49 ms). The mean REE was 14% higher than estimated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(70 citation statements)
references
References 26 publications
4
63
0
3
Order By: Relevance
“…HIV disease is associated with loss of lean (Kotler et al, 1985;Ott et al, 1993) and fat (Mulligan et al, 1997b;Sharpstone et al, 1996) body mass, as a result of opportunistic infections (Paton et al, 1997), metabolic (Melchior et al, 1991;Mulligan et al, 1997a) and hormonal (Strawford & Hellerstein, 1998) changes, decreased food intake and nutrient malabsorption (Kotler, 1998). In women, HIV-related weight loss occurs largely at the expense of body fat (Grinspoon et al, 1997;Kotler et al, 1999), and mean prepregnancy weight of HIV-positive women has been found to be lower than that of HIV-negatives in African settings (Castetbon et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…HIV disease is associated with loss of lean (Kotler et al, 1985;Ott et al, 1993) and fat (Mulligan et al, 1997b;Sharpstone et al, 1996) body mass, as a result of opportunistic infections (Paton et al, 1997), metabolic (Melchior et al, 1991;Mulligan et al, 1997a) and hormonal (Strawford & Hellerstein, 1998) changes, decreased food intake and nutrient malabsorption (Kotler, 1998). In women, HIV-related weight loss occurs largely at the expense of body fat (Grinspoon et al, 1997;Kotler et al, 1999), and mean prepregnancy weight of HIV-positive women has been found to be lower than that of HIV-negatives in African settings (Castetbon et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, the equations of Melchior et al 12,13 were the only ones showing strong concordance with IC values, having been developed for HIV-infected individuals and considering muscle mass as the variable. The equation published in 1991 13 was based on 50 HIV-infected individuals with a diagnosis of AIDS, with the presence of opportunistic infections or Kaposi sarcoma, with the presence of cachexia and the absence of antiretroviral use.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive equations of resting energy expenditure for HIV-infected individuals. 14 Cunningham 10 Melchior et al 13 Melchior et al 12 Resting Harris-Benedict 11 Schofield 14 Cunningham 10 Melchior et al 13 Melchior et al were observed between IC and the Cunningham 10 and Harris & Benedict 11 equations. …”
Section: Ic and Ree Predictive Equationsmentioning
confidence: 99%
See 2 more Smart Citations